Acute transplantation of NPC on electrospun poly-lactic acid membranes containing curcumin into the injured spinal cord reduces neuronal degeneration - Sánchez-Martín, María del Mar; Giraldo, Esther; Gisbert Roca, Fernando; Alastrue-Agudo, Ana; Martínez-Ramos, Cristina; Monleón Pradas, Manuel; Moreno-Manzano, Victoria (Frontiers in Biomaterials Science, 2023)
Effective spinal cord injury (SCI) treatment remains a significant challenge, given the complex nature of the primary injury and associated devastating loss of neural activity. Neural progenitor cell (NPC)-based therapy has emerged as a potent strategy for the treatment of SCI. However, the invasive nature of direct cell transplantation and the need to enhance graft integration into host tissue remain critical issues. We implemented an improved combinatorial approach to SCI treatment by functionalizing electrospun poly-lactic acid (PLA) membranes that support the sustained delivery of curcumin (PLA-curcumin) and act as a carrier for NPC for local transplantation. In vitro experiments demonstrate that curcumin prevents harmful oxidative and inflammatory stress by preventing death and inhibiting NF-B activation (mimicked by treatment with hydrogen peroxide or lipopolysaccharide acid). Curcumin also enhances neuritelike outgrowth in NPC and cortical neurons in culture, which may enhance neural connectivity.In vivo transplantation of NPC on a PLA-curcumin electrospun membrane enables cell migration, reduces injured area size, and increases neuronal fiber preservation to induce a slowing of acute neural damage.